Three essays on entrepreneurship and personal finance - Potter, Derek (Kansas State University, 2019)
Self-employment and the operation of private businesses form an important sector of the U.S. labor market, accounting for over 400,000 new organizations launched annually in recent years and nearly two-thirds of job creation according to the Small Business Administration. Yet, ownership of a business is fraught with financial risks, leading some economists to suggest that the average lifetime earnings of private business owners trail those of traditional employment. The three essays that follow explore (a) the motives that may drive people to pursue entrepreneurship despite the financial risk, (b) the asset allocation behavior of practicing entrepreneurs, and (c) the resulting satisfaction levels of those who transition into entrepreneurship. The first essay examines a population of users in the pre-launch phase of business development. Past research has suggested that given the lower expected financial returns from entrepreneurship that motivations to launch a business might be driven by preferences for high degrees of autonomy, overly optimistic assessments of financial outcomes, or higher risk preferences. Measures of each of these phenomena are included in a cohesive model guided by the Theory of Planned Behavior along with other relevant variables. Logistic regression predicting intent to launch a business in the future reveals that more general attitudes towards entrepreneurship increase the likelihood of interest in business ownership, while financial motivations are tied to decreased likelihood. The second essay examines the impact of business ownership during the operation of the business. Granted that business owners possess illiquid private organizations, Modern Portfolio Theory might predict that they reduce exposure to other risky asset classes (e.g., stocks). This essay examines stock ownership with consideration given to entrepreneurial status as well as the level of risk exposure stemming from owning a business. Logistic regression using data from the 2016 Survey of Consumer Finances reveals that business owners are less likely to participate in the stock market. An Ordinary Least Squares regression modeling the ratio of equity to total financial assets, however, reveals no significant differences in levels of equity ownership among business owners and the traditionally employed. Collectively, these findings may indicate that entrepreneurs face initial barriers to stock market investment that later fade if participation in the equity market does begin. Finally, the third essay utilizes longitudinal 2008-2014 Health and Retirement Study data to examine levels of job, financial, and life satisfaction. Variable selection is guided by the Job-Demand-Control model, and three random effects cumulative logits are produced. Findings suggest that transitions into entrepreneurship are associated with increased odds of job satisfaction but reduced odds of financial or life satisfaction. Results from these three studies imply that individuals might pursue entrepreneurship for non-financial reasons. However, engaging in the launch of a business could affect financial decision making and asset allocation behavior, as well as subsequent levels of satisfaction with personal finances and life. Implications for organizations and professionals who support prospective entrepreneurs are discussed.
Keywords: Entrepreneurship; Business ownership; Personal finance; Entrepreneurship motivation; Business owner portfolios